Moral disengagement and empathy in cyberbullying: how they are related in reflection activities about a serious game - Sofia Mateus Francisco; Paula Costa Ferreira; Ana Margarida Veiga Simão; Nádia Salgado Pereira (BMC Psychology, 2024)
Abstract Cyberbullying is a complex phenomenon with multiple factors involved, both contextual and individual factors, such as moral disengagement and empathy. This study investigated how moral disengagement and empathy could be related, longitudinally in cyberbullying events. Specifically, two gamified tasks (one for empathy and other for moral disengagement) were analyzed. These tasks were developed attending to the specificities of the cyberbullying scenarios presented in a serious game. To accomplish this goal, data from gamified tasks (N = 208), from 4 different moments, were analyzed through multilevel linear modeling. Results suggested that there was a change in adolescents’ moral disengagement over time. Participants with greater empathy revealed lower moral disengagement overall. Over time, adolescents with greater empathy revealed lower moral disengagement within their own growth rate. Overall, our results provide important information about the dynamic relationship between moral disengagement, empathy and cyberbullying, which informs future studies and interventions.